The Red Sea species of Cymo de Haan, 1833 (Decapoda, Brachyura, Xanthidae), associates of scleractinian corals - Brösing, Andreas; Al-Aidaroos, Ali M.; Türkay, Michael (Zootaxa, 2014)
Four species of Cymo, associates of scleractinian corals, from the Red Sea were studied using scanning electron and light microscopy. Characters based on the morphologies of the carapace, gonopods and digestive tract (gastric teeth) were investigated and described in detail. All Red Sea species are redescribed, distinguishing characters are identified and an identification key is provided. Cymo quadrilobatus is the most distinctive species, with prominent granules on the carapace and most of the surfaces of the chelipeds and walking legs, and four red spots on the dorsal surface of the carapace in contrast to the smooth or finely granular surfaces in the other three species. Cymo deplanatus is listed as new record for the Red Sea.